Penerapan Fungsi Manajemen Gereja di GBI ROCK Pondok Indah Jakarta Selatan - Hannyta, Chrisna; Sumito, Ronny Dwikora; Pieter, Roy (STT Kingdom, 2024)
This study aims to determine the application of management functions (planning, organizing, actuating and controlling) of the church at GBI ROCK Pondok Indah Jakarta. This is descriptive qualitative research; the key persons are professional worker who are also as church full-timers. Data were collected through structured interviews, then analyzed using the stages of condensation, data display, conclusion drawing. The results showed that the application of church management functions at GBI ROCK Pondok Indah South Jakarta that are related to the planning, actuating, organizing and controlling system has not been achieved optimally, because it has inhibiting factors, namely communication, policies that are considered less strategic and dynamic. Church full-timers who are given trust do not understand their duties and responsibilities, the church provides corrections to the program but is personal.